2013
DOI: 10.1155/2013/537279
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Genotoxicity Evaluation of Organochalcogens in Human Leucocytes: A Comparative Study between Ebselen, Diphenyl Diselenide, and Diphenyl Ditelluride

Abstract: Organochalcogens, particularly ebselen, have been used in experimental and clinical trials with borderline efficacy. (PhSe)2 and (PhTe)2 are the simplest of the diaryl dichalcogenides and share with ebselen pharmacological properties. In view of the concerns with the use of mammals in studies and the great number of new organochalcogens with potential pharmacological properties that have been synthesized, it becomes important to develop screening protocols to select compounds that are worth to be tested in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Recently, our research group demonstrated that organoselenium and organotellurium present hemolytic and genotoxic effects in human blood cells ( Santos et al, 2009a ; Santos et al, 2009b ; Caeran Bueno et al, 2013 ), which is in accordance with results published by other laboratories in experimental bacteria and rodent models ( Degrandi et al, 2010 ). Similarly, organoselenides and tellurides can be toxic in different in vivo and in vitro models of animal pathologies ( Maciel et al, 2000 ; Taylor, 1996 ; Stangherlin, Rocha & Nogueira, 2009 ; Moretto et al, 2007 ; Heimfarth et al, 2011 ; Heimfarth et al, 2012a ; Heimfarth et al, 2012b ; Comparsi et al, 2012 ).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Recently, our research group demonstrated that organoselenium and organotellurium present hemolytic and genotoxic effects in human blood cells ( Santos et al, 2009a ; Santos et al, 2009b ; Caeran Bueno et al, 2013 ), which is in accordance with results published by other laboratories in experimental bacteria and rodent models ( Degrandi et al, 2010 ). Similarly, organoselenides and tellurides can be toxic in different in vivo and in vitro models of animal pathologies ( Maciel et al, 2000 ; Taylor, 1996 ; Stangherlin, Rocha & Nogueira, 2009 ; Moretto et al, 2007 ; Heimfarth et al, 2011 ; Heimfarth et al, 2012a ; Heimfarth et al, 2012b ; Comparsi et al, 2012 ).…”
Section: Introductionsupporting
confidence: 90%
“…The results presented here indicate clear toxic effects of (PhTe) 2 when compared with (PhSe) 2 . Tellurium (Te) has the potential of redox cycling which leads to formation of reactive oxygen species (ROS) which can damage biomolecules ( Maciel et al, 2000 ; Nogueira, Zen & Rocha, 2004 ; Santos et al, 2009a ; Santos et al, 2009b ; Degrandi et al, 2010 ; Sailer et al, 2004 ; Caeran Bueno et al, 2013 ). Organotellurium-induced intracellular ROS accumulation has been reported to be the cause of cell death in HL-60 and different types of cancer cells ( McNaughton et al, 2004 ; Sandoval et al, 2010 ; Ding et al, 2002 ; Rigobello et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interesting studies about the toxicity of Ph 2 Te 2 are available in the literature [20,21,22,23,24]. However, the toxicological data on Ph 2 Te 2 and organotellurium compounds, in general, are not exhaustive and conflicting results were obtained, the majority of which lean towards the view that organotellurides have a higher toxicity compared to their selenium analogs [25].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of molecular targets are modulated by ebselen including: NADPH oxidase 2 [150,151], H + /K + ATPase transporter [152], Ca 2+ - and phospholipid-dependent protein kinase C [151], lipoxygenase [153], thioredoxin reductase [154], and metallothionein [155]). Moreover, cellular toxicity in leukocytes and hepatocytes has been reported, further reducing the likelihood of ebselen’s use in clinical practice [156,157].…”
Section: Pharmacological Inhibition Of Ddahmentioning
confidence: 99%